Public and private supply of beds and access to health care in the COVID-19 pandemic in Brazil - Conte, Danielle (2020)
The COVID-19 pandemic, a global health crisis, has put health systems in several countries in check. In Brazil, patient care has brought about disparities in the offer and access to public and private services and initiatives to preserve healthcare segmentation. The work systematizes information about: beds for hospitalization by COVID-19; patients´ complaints claiming access; and actions to expand the supply of assistance resources involving government proposals and the private sector (health plan companies and hospitals). There was an expansion of hospital beds, but the uneven distribution in the regions of the country has not changed. Nor does it appear to have changed the pattern of coverage control by health insurance companies. A significant portion of the analyzed legal actions refers to the denial of access to private plan clients due to a contractual deficiency, while SUS patients claimed a place in the ICU. Lives were lost due to omissions for effective and qualified protection. Public intensive care units had maximum occupancy, while the private sector accounted for idle beds. The analysis shows barriers to access to beds and resistance to attempts to unify public and private efforts to mitigate lethality by the new coronavirus.